TRANSAKSI CRYPTOCURRENCY DITINJAU DALAM PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Auranti, Sagita; Asyiqin, Hisyam (LPPM STIH Awang Long, 2024)
The Globalization system has had a huge impact on modern society, especially in the fields of science, technology, information and communication, all of which are developing rapidly. The most famous currency is Bitcoin or cryptocurrency. Because there are now no clear boundaries and no recognition of the existence of cryptocurrencies in Indonesia, these cryptocurrencies are facing a number of polemics regarding their use throughout the world, including in that country. The debate over whether Bitcoin is halal or haram in Islam continues among scholars who study the Koran, hadith, ijma and other Islamic books. One important area of expertise in the world of information security is cryptography. Today, professionals in the fields of computer science and mathematics discovered a new application of encryption that could improve the quality of life of local communities: the buying and selling of digital currencies known as cryptocurrencies. Digital currencies that are not subject to government regulation are known as cryptocurrencies; this does not include official cash. This cryptocurrency is the forerunner to the creation of digital currency which is now known as Bitcoin currency, which can be used like other types of money. And the result of the discussion is that whether scholars allow cryptocurrency or not. This research uses a qualitative method where this method focuses on in-depth observation. Therefore, the use of qualitative methods in this research can produce a study of a phenomenon that is more comprehensive with literature research. Based on the background information provided previously, the author identifies problems that require further investigation. Among other things, what is the meaning of cryptocurrency in the current understanding and context and what is Islamic law regarding the use of cryptocurrency as a transaction tool.